Reflections on establishing an effective and sustainable community of practice for a strategic objective within a higher education institution. (20th March 2023) - Bastiaens, Ellen; Heymann, Perry
Abstract: Communities of practice (CoPs) have received much attention since the introduction of this concept in the early nineties. Most CoPs in higher education address teaching and learning for specific subject matter, or professional development focusing on the student or the teacher. In our case study, we developed a CoP around a strategic objective for our institution: addressing the enhancement of the employability of our students. This article presents our investigation of what features are key for an effective and sustainable CoP that facilitates the achievement of a strategic objective in a higher education institution (HEI). We used a case study analysis to identify key ingredients that contribute to establishing an effective and sustainable CoP: (1) installing a core group as catalyst; (2) defining a common language connecting strategy, theory and practice; (3) appointing the facilitator; (4) creating an open atmosphere in and around the community; (5) create close involvement in the CoP with the already‐standing organisation to ensure long‐lasting and sustainable continuation of a CoP. Next to the evaluation of key features for the CoP, we also reflected on design thinking as integral to facilitating the community's practice.